2022
DOI: 10.1021/acsapm.2c01494
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Physical Bonds Cross-Linked Strong and Tough Hydrogel with Antibacterial Ability for Wearable Strain Sensor

Abstract: Strong, tough, and antibacterial hydrogels are promising in the fields of human motion detection and wearable electronics. However, it remains challenging to reach the antibacterial ability without losing the mechanical properties. In this work, strong and tough Fe3+-sodium alginate/poly(acrylamide-co-acrylic acid)/Ag nanowire (Fe3+-SA/P(Am-co-Ac)/AgNWs) hydrogel with antibacterial ability was facially prepared using multiple physical bonds. The superior mechanical properties are ensured by the double network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Consequently, the AgNWs incorporated in the hydrogels lead to the inhibition of bacterial growth. [ 49,50 ] In addition, as shown in Figure S16a,b (Supporting Information), it can be observed that the bactericidal rate of S‐PPA is relatively lower compared to PPA. This is mainly due to the presence of a skin layer in S‐PPA, which hinders the contact between the hydrogel and bacteria.…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, the AgNWs incorporated in the hydrogels lead to the inhibition of bacterial growth. [ 49,50 ] In addition, as shown in Figure S16a,b (Supporting Information), it can be observed that the bactericidal rate of S‐PPA is relatively lower compared to PPA. This is mainly due to the presence of a skin layer in S‐PPA, which hinders the contact between the hydrogel and bacteria.…”
Section: Resultsmentioning
confidence: 97%
“…AcAgNWs) hydrogels with 99.98% and 99.95 inhibition rates against E. coli and S. aureus , respectively, and the prepared robust, tough, and antibacterial hydrogels can be applied to human motion detection and wearable electronics. [ 211 ] Lei and Wu designed an amphoteric hydrogel in terms of molecular interactions, and the prepared hydrogel successfully combined high strength, hyperstretchability, self‐healing (within 12 h at room temperature), 3D printing, apparent stimulus responsiveness, biocompatibility, and antimicrobial activity, can be used to design multifunctional zwitterionic hydrogel skin. ( Figure a).…”
Section: Biomedical Potential Of Antibacterial Hydrogels With Fixed A...mentioning
confidence: 99%